Pengaruh Pengungkapan Corporate Social Responsibility dan Good Corporate Governance Terhadap Nilai Perusahaan - Nyoman Trisna Parwata; I Wayan Gde Wahyu Purna Anggara (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This study aims to determine the effect of corporate social responsibility disclosure and good corporate governance on company value. This research was conducted on all companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The method of determining the sample using non-probability sampling method with purposive sampling technique and obtained 170 observations. The data collection method uses non-participant observation. The data analysis technique used is Partial Least Squares-Structural Equation Model. The results of the study show that corporate social responsibility disclosure has no significant effect on company value and good corporate governance has a significant positive effect on company value which means that the higher the corporate social responsibility disclosure will not affect the stock value and with the implementation of good corporate governance, the higher of company value is reflected in the stock price as well. The implications of this research show the application of signal theory, stakeholder theory, and agency theory as well as providing benefits to parties who need it, especially companies and stakeholders related to companies in expressing corporate social responsibility disclosure and improving good corporate governance which can increase company value.